A randomized trial comparing the intraoperative durability of double-gloving with Biogel® surgical gloves to 3 comparators - Michelle Doll; Asmaa Namoos; Le Kang; Jibanananda Satpathy; Michael J. Feldman; Anthony Cassano; Jaime Bohl; Michel B. Aboutanos; Brian Cameron; Jason Kim; Celine Asbury; Mahdee Haque; et al. (Cambridge University Press, 2024)
Abstract Objective: To determine and compare the intraoperative durability of 4 major surgical glove brands. Design, Setting, and Participants: This study is a randomized open-label clinical trial in which surgical gloves from 4 manufacturers are randomized to 5 surgical subspecialty study groups: (1) orthopedic surgery, (2) neurosurgery, (3) colorectal surgery, (4) trauma or acute general surgery, and (5) cardiac and plastic surgeries. The study was divided into 10 periods, with a cross-over design, and was conducted at a tertiary care academic medical center. Participants were licensed and certified physicians, physicians-in-training, scrub nurses, or technicians working within the sterile field. Interventions: Participants from each study group were randomly assigned to 1 of 4 surgical glove manufacturer types and subsequently rotated through the other 3 glove brands such that each participant acted as their own control in the sequential cross-over design. Main Outcomes and Measures: The primary outcome was to determine and compare the intraoperative failure rate of Biogel® Sterile Surgical undergloves against sterile surgical undergloves from 3 other manufacturers, both as a combined competitor group and individually. Results: There were no differences between brands with respect to the primary outcome of underglove intraoperative failures. Brand 1 wearers were slightly more likely to detect glove failures when they occurred. Conclusion: The durability of surgical gloves intraoperatively is similar across 4 major glove manufacturers. Detection of intraoperative failures is infrequent, though specific glove characteristics may promote enhanced detection. Recognition of glove perforations intraoperatively is important in the maintenance of a maximally sterile field. Trial Registration: ClinicalTrials.gov Identifier: NCT03344354.